Kindler's syndrome: A rare case report - Suman, Neelam (Medknow Publications & Media Pvt Ltd, 2014)
Kindler syndrome is a rare hereditary disorder, associated with skin fragility. The syndrome involves the skin and mucous membrane with radiological changes. The genetic defect has been identified on the short arm of chromosome 20. This report describes a 16-year-old patient with classical features like blistering and photosensitivity in childhood and the subsequent development of poikiloderma.